The Religious Beliefs and Practices of Santal Tribe in Mayurbhanj District of Odisha: Role of Santal Women. - Hembram, Mayamani; Tripathy, Sishir Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The Santal Tribe have different classes of Santal gods. One of the most contemplated, the Santal religion venerates Marang buru or Bonga as the Supreme Deity. Most of adoration, be that as it may, falls on a court of spirits (Bonga), who handle various parts of the world and who are pacified with petitions and contributions so as to avoid underhanded impacts. These spirits work at the town, family, predecessor, and sub- tribe level, alongside detestable spirits that cause ailment and can occupy town limits, mountains, water, tigers, and the timberland. A trademark highlight of a Santal town is a consecrated woods (known as the Jahe or "Santal Santhal") on the edge of the town where numerous spirits live and where a progression of yearly celebrations occur. The Naturally emerges if the strict acts of the Santal are not some type of a functioning love of certain gods and lesser spirits, along with an obscure confidence in spirits and a future presence implied by the term ’Animism’. One is confounded to think, as seemed to be, with respect to what is the specific thought of the Santal when he thinks about the spirits, state of the slopes. Is it a veneration for the spirits of the substance. He think he is in dangerbof being demolished by it. At the point when a Santal thinks about a tiger-soul, tiger- force or tiger-evil presence, the pith and model, all things considered. The Santal are spirits Thakur Jiu or Dhorom, Ancestor Spirits specifically love of the Pitris.